2018
DOI: 10.4025/psicolestud.v23i0.40289
|View full text |Cite
|
Sign up to set email alerts
|

Preocupações E Comportamentos Relacionados À Aparência Física Na Infância: Uma Abordagem Qualitativa

Abstract: Orcid: https://orcid.org/0000-0002-5240-6710 Juliana Fernandes Filgueiras Meireles 2 , Orcid: https://orcid.org/0000-0001- Fabiane Frota da Rocha Morgado 3 , Orcid: https://orcid.org/0000-0002-3969-9029 Maria Elisa Caputo Ferreira 4 , Orcid: https://orcid.org/0000-0002-3294-7560 RESUMO:A criança elabora mecanismos internos para formação de referências do próprio corpo, desde a tenra idade, tornando-se uma fase da vida relevante para estudiosos. Objetivou-se investigar atitudes relacionadas à imagem corporal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Tatangelo and Ricciardelli (2013) point out that 'being in shape' is an aspect of the ideal body highlighted by boys and girls. More recently, the study of Neves et al (2018) points out that the children evaluated presented attitudes that indicated concern with the body, in general, and specific aspects, besides behaviors related to body image.…”
Section: Introductionmentioning
confidence: 99%
“…Tatangelo and Ricciardelli (2013) point out that 'being in shape' is an aspect of the ideal body highlighted by boys and girls. More recently, the study of Neves et al (2018) points out that the children evaluated presented attitudes that indicated concern with the body, in general, and specific aspects, besides behaviors related to body image.…”
Section: Introductionmentioning
confidence: 99%
“…Tatangelo e Ricciardelli (2013) apontam que estar em forma foi um aspecto do corpo ideal destacado por meninos e meninas. Mais recentemente, identificase o estudo de Neves et al (2018), que aponta que as crianças avaliadas apresentaram atitudes que indicam preocupação com o corpo em aspectos gerais e específicos, além de comportamentos relacionados com a imagem corporal.…”
Section: Introductionunclassified